Internalisasi Nilai-nilai Moderasi Beragama dalam Pembelajaran PAI di SMA Al-Biruni Cerdas Mulia Kota Bandung - Gunawan, Heri; Ihsan, Mahlil Nurul; Jaya, Encep Supriatin (Atthulab: Islamic Religion Teaching and Learning Journal, 2021)
Abstract: This study explains the concept of internalizing the values of religious moderation in Islamic Education learning at SMA Cerdas Mulia Bandung. Moderation is very important to be applied in everyday life to uphold unity, benefit, goodness and world peace. One of the efforts to establish religious moderation can be applied through education, namely the inclusion of religious moderation values in Islamic Islamic education learning in schools. This study used a qualitative field approach using analytical descriptive methods. The data collection techniques of this study were interviews, observation and documentation, while the respondents of this study were addressed to Islamic Education teachers and students of SMA Cerdas Mulia Bandung. The results of this study explain that the internalization of religious moderation values can be developed through Islamic Education learning, then it can be applied through religious coaching which is carried out through planning, implementing and evaluating Islamic Education learning so that finally the students’ religious moderation is formed. Â Abstrak: Penelitian ini menjelaskan konsep internalisasi nilai-nilai moderasi beragama pada pembelajaran PAI di SMA Cerdas Mulia Kota Bandung. Moderasi sangat penting diterapkan di dalam kehidupan sehari-hari untuk menjunjung tinggi persatuan, kemaslahatan, kebaikan dan perdamaian dunia. Salah satu upaya dalam membentuk moderasi beragama dapat diaplikasikan melalui pendidikan yakni memasukan nilai-nilai moderasi beragama dalam pembelajaran PAI di sekolah. Penelitian ini menggunakan pendekatan kualitatif lapangan dengan menggunakan metode deskriptif analitik. Adapun teknik pengumpulan data penelitian ini adalah wawancara, observasi dan dokumentasi, sedangkan respoden penelitian ini ditujukan kepada guru PAI dan siswa SMA Cerdas Mulia Kota Bandung. Hasil penelitain ini menjelaskan internalisasi nilai-nilai moderasi beragama dapat dikembagnkan melalui pembelajaran PAI, kemudian dapat diaplikasikan melalui pembinaan keagamaan yang dilakukan melalui perencanaan, pelaksanaan dan evaluasi pembelajaran PAI sehingga akhirnya terbentuklah sikap moderasi beragama peserta didik.